Retrospective process of creating pencak silat artistic performance for beginners - Kurniati Rahayuni (Physical Education Departement of University PGRI Jombang, 2025)
As an activity, pencak silat has four dimensions: as a sport, as a self-defense discipline, as a mental-spiritual training and and as an art. As an art form, pencak silat can be a cultural performance accompanied by music. The appearance of pencak silat as an art performance can provide entertainment based on traditional arts and culture and can be performed at various national and international ceremonial events, and recently competed officially under category of solo creative performance. This paper is part of the report of a community service which was carried out with the aim of socializing and educating pencak silat as artistic performance for the Indonesian community living in Singapore. The activities were pencak silat artistic performance and a short workshop on artistic pencak silat. The highlight of this paper is in the retrospective accounts on creating rthe pencak silat as part of artistic performance, which involving several processes such as: 1) Determining the theme of the performance; 2) Determining the music to accompany the pencak silat performance; 3) Process of developing the movement choreography; 3) Simulation and dry run. Cosidering pencak silat as a growing practice in Indonesia and Internationally, this retrospective process of making pencak silat artistic performance has been recorded and written as it might be beneficial as reference for researcher, teacher, pencak silat coaches and athletes when creating pencak silat artistic performance.